How Proactive Teachers Become Committed: Work Engagement as a Key Mechanism in the Indonesian Education Context - Ifna Ratrika Enggarsari; Olievia Prabandini Mulyana (Utan Kayu Publishing, 2026)
In education, teachers play a role in carrying out their duties as an educator for the continuity of education. Based on data the percentage of teachers experiencing fatigue and turnover tends also be high. This study was conducted with the aim of empirically determining the relationship between Proactive Personality and Job Commitment with Works Engagement as a mediator. This study used a quantitative method with purposive sampling technique and involved 112 elementary school teachers as the research sample. Three primary scales were used in this study, Proactive Personality with the Proactive Personality Scale (PPS), Organizational Commitment Questionnaire (OCQ), and Work Engagement UWES-9 (Utrecht Work Engagement Scale-9). Mediation analysis was performed using Hayes 5.0 PROCESS Macro with bootstrapping was performed 10,000 times with a 95% confidence interval. The Result showed that proactive personality had a significant effect on job commitment with work engagement as a partial mediator (b = 0.31 and 95% significant with CI = 0.16, 0.51). Proactive personality had a significant effect on work engagement (b = 0.35 and p less than 0.001). Work engagement had a significant on job commitment (b = 0.89 and p less than 0.001). This study found that work engagement has a partial effect on the relationship between proactive personality and job commitment.